The Teaching Strategy of Bahasa Indonesia in Curriculum 2013 - Nugroho Aji, Wisnu; Budiyono, Sri (International Journal of Active Learning, 2018)
This article is intended to explain and describe the implementation of Curriculum 2013 on Bahasa Indonesia. A plan of choosing learning strategy of Bahasa Indonesia is supposed to be adapted to the characteristics and approach of the curriculum. It also works for Curriculum 2013 which recommends five stages of scientific approach: observing, asking, trying, associating, and communicating. Based on the characteristics and scientific approach, some learning strategies which are in line with Curriculum 2013 scheme are found. They are (a) Expository Learning Strategy, (b) Contextual teaching and learning (CTL), (c) Inquiry Learning Strategy, and (d) Problem-Based Learning Strategy (PBLS).